Glycaemic control in diabetic rats treated with islet transplantation using plasma combined with hydroxypropylmethyl cellulose hydrogel. (15th January 2020) - Schaschkow, Anaïs; Sigrist, Séverine; Mura, Carole; Barthes, Julien; Vrana, Nihal Engin; Czuba, Elodie; Lemaire, Florent; Neidl, Romain; Dissaux, Caroline; Lejay, Anne; Lavalle, Philippe; Bruant-Rodier, Catherine; et al.
Abstract: Islet transplantation is one of the most efficient cell therapies used in clinics and could treat a large proportion of patients with diabetes. However, it is limited by the high requirement of pancreas necessary to provide the sufficient surviving islet mass in the hepatic tissue and restore normoglycaemia. Reduction in organ procurement requirements could be achieved by extrahepatic transplantation using a biomaterial that enhances islet survival and function. We report a plasma-supplemented hydroxypropyl methylcellulose (HPMC) hydrogel, engineered specifically using a newly developed technique for intra-omental islet infusion, known as hOMING (h-Omental Matrix Islet filliNG). The HPMC hydrogel delivered islets with better performance than that of the classical intrahepatic infusion. After the validation of the HPMC suitability for islets in vivo and in vitro, plasma supplementation modified the rheological properties of HPMC without affecting its applicability with hOMING. The biomaterial association was proven to be more efficient both in vitro and in vivo, with better islet viability and function than that of the current clinical intrahepatic delivery technique. Indeed, when the islet mass was decreased by 25% or 35%, glycaemia control was observed in the group of plasma-supplemented hydrogels, whereas no regulation was observed in the hepatic group. Plasma gelation, observed immediately post infusion, decreased anoïkis and promoted vascularisation. To conclude, the threshold mass for islet transplantation could be decreased using HPMC-Plasma combined with the hOMING technique. The simplicity of the hOMING technique and the already validated use of its components could facilitate its transfer to clinics. Statement of significance: One of the major limitations for the broad deployment of current cell therapy for brittle type 1 diabetes is the islets' destruction during the transplantation process. Retrieved from their natural environment, the islets are grafted into a foreign tissue, which triggers massive cell loss. It is mandatory to provide the islets with an 3D environment specifically designed for promoting isletimplantation to improve cell therapy outcomes. For this aim, we combined HPMC and plasma. HPMC provides suitable rheological properties to the plasma to be injectable and be maintained in the omentum. Afterwards, the plasma polymerises around the graft in vivo, thereby allowing their optimal integration into their transplantation site. As a result, the islet mass required to obtain glycaemic control was reduced by 35%. Graphical abstract: Image, graphical abstract